Impact of gamification on school engagement: a systematic review - Ruiz, Judy Julieth Ramírez; Sanchez, Ana Dolores Vargas; Figueredo, Oscar Rafael Boude (Frontiers in Education, 2024)
School engagement is defined as students’ dedication to activities empirically linked to desired outcomes. This concept encompasses all dimensions of being: academic, emotional, and behavioral. Gamification is presented as an innovative strategy in the field of education because using game design elements can engage students in the learning process. This systematic review sought to analyze the development of research in the academic literature on gamification as a strategy to favor school engagement in primary and secondary education, conducted between 2013 and 2023. A total of n = 90 interventions that met the inclusion criteria were identified using the PRISMA methodology guidelines. The results show that there is a need to evaluate school engagement from a broader perspective when using the gamification strategy and to identify other elements that are necessary to achieve the proposed objectives in the teaching and learning process. Findings also demonstrate that it is important to consider a more holistic view that includes not only motivation and participation, but also other factors and dimensions of school engagement.